Pengaruh Theory Of Planned Behavior Terhadap Minat Kewirausahaan Mahasiswa Universitas Tarumanagara - Felya Felya; Herlina Budiono (Jurnal Manajerial Dan Kewirausahaan, 2020)
The purpose of this study is to find out 1) whether there is an effect of Attitude on Entrepreneurship Intention, 2) whether there is an influence of the Subjective Norms on Entrepreneurship Intention, 3) whether there is an influence of Perceived Behavioral Control on Entrepreneurship Intention, 4) whether there is an influence of Short term Risk Taking on Entrepreneurship Intention, 5) whether there is an influence of Psychological Wellbeing on Entrepreneurship Intention. The population in this study were students of the Faculty of Economics, Tarumanagara University, class of 2015 -2018. The sample used in this study was 100 respondents from the Students of the Faculty of Management Economics, Tarumanagara University. The sampling technique used was nonprobability sampling with purposive sampling method. Overall the results of this study are 1) Attitude has a significant effect and positively to Entrepreneurship Intention in Tarumanagara University Faculty of Economics Management Students, 2) Subjective Norms do not significantly influence but remain positive towards Entrepreneurship Intention in Tarumanagara University Faculty of Economics Management Students, 3) Perceived Behavioral Control has a significant effect and positively to Entrepreneurship Intention in Tarumanagara University Faculty of Economics Management Students, 4) Short term Risk Taking has a significant effect and positively to Entrepreneurship Intention in Tarumanagara University Faculty of Economics Management Students, 5) Psychological Wellbeing has a significant effect and positively to Entrepreneurship Intention in Tarumanagara University Faculty of Economics Management Students. Tujuan penelitian ini adalah untuk mengetahui 1) apakah terdapat pengaruh Sikap terhadap Minat Kewirausahaan, 2) apakah terdapat pengaruh Norma Subjektif terhadap Minat Kewirausahaan, 3) apakah terdapat pengaruh Persepsi Kontrol Perilaku terhadap Minat Kewirausahaan, 4) apakah terdapat pengaruh Pengambilan Risiko Jangka Pendek terhadap Minat Kewirausahaan, 5) apakah terdapat pengaruh Kesejahteraan Psikologis terhadap Minat Kewirausahaan. Populasi dalam penelitian ini adalah Mahasiswa Fakultas Ekonomi Universitas Tarumanagara angkatan 2015-2018. Sampel yang digunakan pada penelitian ini yaitu 100 responden Mahasiswa Fakultas Ekonomi Manajemen Universitas Tarumanagara. Teknik pengambilan sampel yang digunakan yaitu non probability sampling dengan metode pengambilan sampel purposive sampling. Secara keseluruhan hasil dari penelitian ini yaitu 1) Sikap berpengaruh signifikan dan positif terhadap Minat Kewirausahaan Mahasiswa Fakultas Ekonomi Manajemen Universitas Tarumanagara, 2) Norma Subjektif tidak berpengaruh secara signifikan namun tetap positif terhadap Minat Kewirausahaan Mahasiswa Fakultas Ekonomi Manajemen Universitas Tarumanagara, 3) Persepsi Kontrol Perilaku berpengaruh signifikan dan positif terhadap Minat Kewirausahaan Mahasiswa Fakultas Ekonomi Manajemen Universitas Tarumanagara, 4) Pengambilan Risiko Jangka Pendek berpengaruh positif dan signifikan terhadap Minat Kewirausahaan Mahasiswa Fakultas Ekonomi Manajemen Universitas Tarumanagara, 5) Kesejahteraan Psikologis berpengaruh positif dan signifikan terhadap Minat Kewirausahaan Mahasiswa Fakultas Ekonomi Manajemen Universitas Tarumanagara.